2020
DOI: 10.21203/rs.3.rs-26669/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatiotemporal variability and trends in rainfall and temperature in Alwero watershed, western Ethiopia

Abstract: Background: Climate analysis at relevant time scales is important for water resources management, agricultural planning, flood risk assessment, ecological modeling and climate change adaptation. This study analyses spatiotemporal variability and trends in rainfall and temperature in Alwero watershed, western Ethiopia. The study is based on gridded monthly rainfall and maximum and minimum temperature data series at a resolution of 4x4 km which were obtained from the National Meteorological Agency of Ethiopia fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…In general, portions of the study areas experienced a significant increase in the trend of annual rainfall. The finding coincides with studies of [19,20]; [24][25][26] who reported an increasing trend of annual rainfall in different parts of the country. The study also coincides with [63][64]69,70] who reported a notable increase in East African rainfall.…”
Section: Plos Climatesupporting
confidence: 91%
See 1 more Smart Citation
“…In general, portions of the study areas experienced a significant increase in the trend of annual rainfall. The finding coincides with studies of [19,20]; [24][25][26] who reported an increasing trend of annual rainfall in different parts of the country. The study also coincides with [63][64]69,70] who reported a notable increase in East African rainfall.…”
Section: Plos Climatesupporting
confidence: 91%
“…Abegaz & Mekoya, [24] also reported a significant decreasing trend in spring (belg) and winter (bega) rainfall and increasing annual and summer (Kiremt) rainfall in central Ethiopia. Likewise, Alemayehu et al [25] showed significantly increasing trends of annual and seasonal rainfall totals in the western part of Ethiopia. Similarly, Belay et al [26] reported an increasing trend of annual, summer (Kiremt) and winter (Bega) rainfall whereas the spring (belg) season rainfall showed a significant decreasing trend in southern Ethiopia.…”
Section: Introductionmentioning
confidence: 93%